2015
DOI: 10.5603/cj.a2014.0086
|View full text |Cite
|
Sign up to set email alerts
|

Members of the emergency medical team may have difficulty diagnosing rapid atrial fibrillation in Wolff-Parkinson-White syndrome

Abstract: Background: Atrial fibrillation (AF) in patients with Wolff-Parkinson-White (WPW) (Cardiol J 2015; 22, 3: 247-252)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Atrial fibrillation (AF) is encountered commonly in the Emergency Department -however, in the presence of a fast-conducting antegrade accessory pathway, it becomes a life-threatening arrhythmia making early recognition vital. In a survey study, only 18% of emergency physicians surveyed identified WPW and less than 10% correctly identified AF 6 -we hope our picture quiz highlights this rarely encountered but potentially fatal arrhythmia.…”
Section: Discussionmentioning
confidence: 87%
“…Atrial fibrillation (AF) is encountered commonly in the Emergency Department -however, in the presence of a fast-conducting antegrade accessory pathway, it becomes a life-threatening arrhythmia making early recognition vital. In a survey study, only 18% of emergency physicians surveyed identified WPW and less than 10% correctly identified AF 6 -we hope our picture quiz highlights this rarely encountered but potentially fatal arrhythmia.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, in a survey study of emergency medicine physicians, this challenging tachyarrhythmia was identified as WPW syndrome by only 18% of responders, while less than 10% of participants identified AF. 2 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, it can be generally stated that atrial fibrillation with WPW is often not diagnosed correctly and should therefore be avoided. In the case of further training, these cases should be addressed [28].…”
Section: Af and Wpw Syndromementioning
confidence: 99%